Periprocedural Antithrombotic Treatment During Acute Mechanical Thrombectomy for Ischemic Stroke: A Systematic Review - van de Graaf, Rob A.; Chalos, Vicky; del Zoppo, Gregory J.; van der Lugt, Aad; Dippel, Diederik W. J.; Roozenbeek, Bob (Frontiers in Neurology, 2018)
Background: More than one third of the patients with ischemic stroke caused by an intracranial large vessel occlusion do not recover to functional independence, despite fast and successful recanalization by acute mechanical thrombectomy (MT). This may partially be explained by incomplete microvascular reperfusion. Some anti-thrombotics, e.g. anti-platelet agents and heparin, may be able to restore microvascular reperfusion. However, anti-thrombotics may also increase the risk of symptomatic intracranial hemorrhage (sICH). The aim of this review was to assess the potential safety and functional outcome of periprocedural anti-platelet or heparin use during acute MT for ischemic stroke. Methods: We systematically searched PubMed, Embase, Medline, Web-of-science and Cochrane for studies investigating the safety and functional outcome of periprocedural anti-platelet or heparin treatment during acute MT for ischemic stroke. The primary outcome was the risk for sICH. Secondary outcomes were functional independence after 3-6 months (modified Rankin Scale [mRS] 0-2) and mortality within 6 months. Results: 837 studies were identified through the search, of which 19 studies were included. The sICH risks of the periprocedural use of anti-platelets ranged from 6% to 17%, and for heparin from 5% to 12%. Two out of four studies reporting relative effects of the use of anti-thrombotics are pointing towards an increased risk of sICH. Among patients treated with anti-platelet agents, functional independence varied from 23 to 60%, and mortality from 18 to 33%. For heparin, this was respectively 19 to 54% and 19 to 33%. The three studies presenting relative effects of anti-platelets on functional independence showed neutral effects. Both studies reporting relative effects of heparin on functional independence found it to increase this chance. Conclusion: Randomized controlled trials investigating the effect of periprocedural anti-thrombotic treatment in MT are lacking. Some observational studies report a slight increase in sICH risk, which may be acceptable because they also suggest a beneficial effect on functional outcome. Randomized controlled trials are therefore warranted to address the question whether the potentially higher risk of sICH could be outweighed by improved functional outcome.